The synthesis of polymeric dual-functional antimicrobial surface based on poly(2-methyl-2-oxazoline) - Pidhatika, Bidhari; Rakhmatullina, Ekaterina (Indonesian Journal of Biotechnology, 2014)
There is a high interest in the development of antimicrobial coatings to fi ght bacterial infections.We present the development of dual-functional antimicrobial surface, in which a biopassive platform wasfunctionalized with bioactive compounds on the surface, using a graft copolymer system poly(L-lysine)-graftpoly(2-methyl-2-oxazoline)-quarternery ammonium compound (PLL-g-PMOXA-QAC). Alkyne functionalitywas introduced to the PMOXA chain at Î±-terminus by initiating the living cationic polymerization of 2-methyl-2-oxazoline with a propargylic-initiator. The reaction was terminated with carboxy derivative-terminator thatallows grafting of the polymeric chain from the Î²-terminus to poly(L-lysine) (PLL) backbone, resulting in graftcopolymer alkynyl PLL-g-PMOXA. The conjugation between alkynyl PLL-g-PMOXA and QAC was thenperformed using click reaction. The chemical structures of the polymers were characterized by MALDI-TOFspectrometry and NMR spectroscopy. The results demonstrate that we have successfully synthesized PLL-g-PMOXA-QAC copolymer with grafting density (number of lysine/number of PMOXA) of 0.33. The resultingPLL-g-PMOXA-QAC copolymer was then immobilized onto carboxylated tissue cultured polystyrene (TCPS)surface and exposed to bacteria solution to test its dual-functional properties. Preliminary live-and-deadbacteria study indicates dual-functionality of the PLL-g-PMOXA-QAC-coated surface.